The Repressed Expressed : Novel Perspectives on African and Black Diasporic Literature - Fishkin, Benjamin Hart; Ankuma, Adaku T., 1956-; Ndi, Bill F. (Book collections on Project MUSE., 2017)
Through multiple points of resistance, The Repressed Expressed underscores how hard it is to build a community in any nation with no beneficial qualities of hope and transparency. This informative collection of essays highlights that wherever stability and order are lacking, the universal appeal is to express that which is suppressed. Also, like a map or guidebook, The Repressed Expressed indicates how people in such geographical prisons strive to transform their agitation into spiritual and political pathways, free of pain and hurt from, and anger towards a dirty and corrupted world. It thus, underpins discord and brings to the fore the authority's penchant for heaping abuse upon those caused to live in fear. In short, The Repressed Expressed is an impressive compilation of literary evidence informing scholarship on opinions and beliefs relating to repression, its expression, and the immeasurable associated cost.